2001
DOI: 10.1097/00001756-200106130-00030
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral protection by hypoxic preconditioning in a murine model of focal ischemia-reperfusion

Abstract: Sublethal periods of hypoxia or ischemia can induce adaptive mechanisms to protect against subsequent lethal ischemic insults in a process known as ischemic preconditioning. In the present study, we developed a murine model of cerebral preconditioning using several common strains of adult mice. Animals were exposed to sublethal hypoxia (11% oxygen for 2 h) 48 h prior to a 90 min period of transient focal middle cerebral artery occlusion, induced by an intraluminal filament; injury was assessed 24 h later by TT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
128
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 29 publications
11
128
3
Order By: Relevance
“…In general, two types of animal models, WbHPC and single-organ HPC, have been described [1,[7][8][9][10][11] . Lu et al created a…”
Section: An Animal Model Of Whole-body Hypoxic Preconditioning (Wbhpc)mentioning
confidence: 99%
“…In general, two types of animal models, WbHPC and single-organ HPC, have been described [1,[7][8][9][10][11] . Lu et al created a…”
Section: An Animal Model Of Whole-body Hypoxic Preconditioning (Wbhpc)mentioning
confidence: 99%
“…Chronic cerebral hypoxia (8% oxygen for 2 weeks) promotes an active and robust vascular remodeling response, which culminates in B50% increased vascular density across all areas of the central nervous system (CNS) (LaManna et al, 2004;Milner et al, 2008a). The value of this model is underscored by the finding that mice exposed to chronic cerebral hypoxia (hypoxic preconditioned) are subsequently protected from focal cerebral ischemia (Miller et al, 2001). In light of the obvious need for arteriogenesis as part of an effective remodeling response after ischemic stroke, and the interesting expression pattern of CD105 on angiogenic vessels, the object of this study was twofold: first, to determine if chronic hypoxia promotes the formation of new arterial vessels, and second, to determine if CD105 preferentially labels angiogenic endothelial cells during hypoxic-induced vascular remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, hypoxic preconditioning also induces tolerance against focal transient (15) and permanent (16) cerebral ischemia in adult mice. These studies suggested that hypoxia-inducible factor-1 (HIF-1) 1 could be an important mediator of hypoxia-induced tolerance to ischemia (13,14,16).…”
mentioning
confidence: 99%